Non-agricultural land use and land reform: theory and evidence from Brazil - Juliano J. Assunç\~ao (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2005)
This paper examines the effect of nonagricultural land use on agrarian organization and land reform, providing a simple model to determine its policy implications and some evidence on its importance. It is argued that, if land-rental market is imperfect, there is a role for redistributive land policies and the following implications hold: (i) land reform is more probable to enhance efficiency in a low-wage economy; (ii) such policies should aim small farmers instead of landless people, obtaining land from large landholders. Empirical evidence suggests this is a relevant issue in Brazil, specially during periods of high macroeconomic instability.
Keywords: 330; land reform; land use; agricultural development; Bodenreform; Landnutzung; Brasilien